(untitled) (Medical Forum Monthly, 2024)
Objectives: To evaluate the financial burden and outcome of the children with brain abscess and underlying congenital cyanotic heart disease. To emphasize the need of early diagnosis and surgery of congenital cyanotic heart disease. Study Design: Cross Sectional Descriptive Study. Place and Duration of Study: This study was conducted at the department of paediatric cardiology The Children’s Hospital and The Institute of Child Health, Multan from February 2010 to January 2012. Patients and Methods: All the patients presenting with brain abscess and having underlying congenital heart disease were included in the study. All the patients underwent transthoracic echocardiography and computed tomography (CT) scan of the brain. Data was taken on a written proforma after proper consent. Results: A total of 58 patients with cyanotic congenital heart disease presented with CNS manifestations including headache, fever, focal neurological signs, fits or altered sensorium during the study period. Out of these 24 turned out to have brain abscess. Multiple brain abscesses were found in 7 patients. All the patients were given broad spectrum IV antibiotics. 19 of the patients required surgical intervention. Repeat CT scan was performed in all the patients. Only 5 patients recovered without any neurological sequalae.7 patients expired during hospital stay. All of the remaining 12 patients survived but with some permanent neurological deficit.IV antibiotics, supportive treatment, CT scan, other laboratory investigations and surgery, all have a lot of cost. Around 1500 to 2000 US , on an average, were spent by the government on one patient during hospital stay. Conclusion: The only way to avoid CNS complications of CCHD is early diagnosis and early surgical treatment. But unfortunately, in this country because of lake of paediatric cardiology services and deficiency of paediatric cardiac surgery centers, corrective surgery of congenital cyanotic heart disease is delayed. It increases the risk of brain abscess formation which in turn leads to excessive financial burden on government resources and also increases the risk of long term neurological sequalae. Establishment of more and more paediatric cardiac surgery centers in this country is urgently required.